Discipline Level Profile Of Class Ix Students at Mts Al-Muhtaddin Bantargebang, Bekasi City - Nazwa Lestari; Yandi Cahya Yundani (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
This study aims to describe the discipline level profile of ninth-grade students at Mts Al-Muhtadin Bantar Gebang, Bekasi City. Discipline is an essential value in life, particularly in the learning process and in shaping students' personalities. A quantitative descriptive method was employed in this study, with data collected through a questionnaire designed using a Likert scale to determine students' discipline levels. The population consisted of all ninth-grade students at Mts Al-Muhtadin, totaling 175 students, while the research sample included 122 students from 38 statement items, resulting in responses from 151 students. The findings indicate that the discipline level among ninth-grade students at Mts Al-Muhtadin is high, with 92.72% in the high category, 7.28% in the moderate category, and no students in the low category. It is expected that this high level of discipline will continue to be maintained and further improved